Teknik Studi Kritis Atas Kitab-Kitab Hadits - Yusyadi Rusli; Tajul Arifin; Ulummudin Ulummudin (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This research examines critical study techniques of hadith collections, focusing on the methods of sanad and matan criticism to assess the authenticity of hadith. Hadith criticism is an academic effort to evaluate the quality of the transmission and the textual content of hadith, ensuring its originality as a source of Islamic teachings after the Qur'an. The approach includes sanad criticism to assess the chain of transmission and the credibility of the narrators, and matan criticism, which evaluates the consistency of the hadith text with the Qur'an and other Islamic principles. This study also analyzes the criticism methods used in major hadith collections like Sahih Bukhari and Sahih Muslim, and explores textual and contextual approaches in understanding hadith. Contemporary challenges in hadith criticism, such as hadith fabrication and the relevance of hadith application in modern contexts, are discussed along with potential solutions. Through appropriate hadith criticism, the teachings of Prophet Muhammad can be authentically understood and relevantly applied in the lives of Muslims. A holistic approach positions hadith criticism as a crucial tool for preserving the purity of Islamic teachings and providing relevant guidance for Muslims across generations.